VD_FINDINFO 22 vom 30. April 2024 - VD Tribunal cantonal (2024)
RÉCUSATION, BAIL À LOYER, ADMISSION DE LA DEMANDE | 47 al. 1 let. f CPC (CH), 47 CPC (CH), 48 CPC (CH), 8a al. 3 CDPJ, 8a al. 4 CDPJ, 8a CDPJ, 8b al. 4 CDPJ